19p13 microduplications encompassing NFIX are responsible for intellectual disability, short stature and small head circumference. (January 2018) - Trimouille, Aurélien; Houcinat, Nada; Vuillaume, Marie-Laure; Fergelot, Patricia; Boucher, Cécile; Toutain, Jérôme; Caignec, Cédric; Vincent, Marie; Nizon, Mathilde; Andrieux, Joris; Vanlerberghe, Clémence; Delobel, Bruno; et al.
Abstract Syndromes caused by copy number variations are described as reciprocal when they result from deletions or duplications of the same chromosomal region. When comparing the phenotypes of these syndromes, various clinical features could be described as reversed, probably due to the opposite effect of these imbalances on the expression of genes located at this locus. TheNFIX gene codes for a transcription factor implicated in neurogenesis and chondrocyte differentiation. Microdeletions and loss of function variants ofNFIX are responsible for Sotos syndrome-2 (also described as Malan syndrome), a syndromic form of intellectual disability associated with overgrowth and macrocephaly. Here, we report a cohort of nine patients harboring microduplications encompassingNFIX . These patients exhibit variable intellectual disability, short stature and small head circumference, which can be described as a reversed Sotos syndrome-2 phenotype. Strikingly, such a reversed phenotype has already been described in patients harboring microduplications encompassingNSD1, the gene whose deletions and loss-of-function variants are responsible for classical Sotos syndrome. Even though thetype/contre-type concept has been criticized, this model seems to give a plausible explanation for the pathogenicity of 19p13 microduplications, and the common phenotype observed in our cohort.